Interferensi Penerjemahan Indonesia-Arab : (Studi Kasus Terhadap Mahasiswa Jurusan Bahasa Dan Sastra Arab Fuad IAIN Metro Lampung) - Susilawati, Ani (STAI Syaichona Moh. Cholil Bangkalan, 2022)
Translation means the transfer of one language to another. In the translation process, of course, you will be faced with linguistic problems and non-linguistic problems. Linguistic problems that often occur such as mastery of vocabulary and mastery of the structure of the source language are low so that in the process of translating words and sentences they experience many obstacles. Meanwhile, non-linguistic factors related to social and cultural aspects such as equivalence in translation. This study aims to reveal meaning deviations in the selection of diction or inappropriate words and sentences that occur due to language interference that occurs in the translator, where the translation results seem stiff and difficult to understand. In addition to choosing the right diction, the translator's sense of language (dzauq) should not be ignored. Because the sense of language arises from the social and cultural side that is automatically attached to a language. This research is a type of library research, which describes a research conducted solely based on facts or phenomena contained in the data. The data is taken from the thesis proposal of BSA FUAD IAIn Metro students. In this study using three stages in the data processing process, namely data collection techniques using listening and note-taking techniques, data analysis techniques using a language approach, and the last technique is the presentation of the results of data analysis carried out by parsing each data. Through these several stages, it can be found that these problems occur due to bilingualism and lack of mastery of the sense of language (dzauqul lughoh).